042 Exploring congenital heart disease with paediatric and adult patients: an interdisciplinary approach using art, medical imaging and 3D printing. (December 2018) - Wray, J; Biglino, G; Hall, S; Layton, S
Abstract : Background: Patients with congenital heart disease (CHD) require follow-up across the life-span. In common with other life-long conditions, responsibility for management of their condition shifts from parents to the patients themselves as they transition from paediatric to adult services, requiring young people to engage and understand their condition and the lifestyle implications of their CHD. Methods: Using an interdisciplinary approach merging medical imaging, 3D printing technology and artistic methodologies, we worked with young people and adults with CHD from three CHD centres. Patients (n=23; 14–48 years) participated in two-part creative workshops facilitated by an artist, health psychologist and bioengineer. A range of creative exercises to facilitate the development of imagery and language to explore individual uniqueness included blindfolded drawing and sculpting self-portraits, creative writing, body mapping and metal embossing. Patient-specific heart images were derived from participants' MRI data. MRI-derived patient-specific heart models were manufactured by 3D printing. Heart-related imagery and narratives were explored through discussion of the models and artistic re-interpretation of the heart images. All patients engaged well with the interdisciplinary process. Results: Heart narratives were powerful and unique and included eloquent metaphors of survival, resilience, strength, fragility and structural complexity. Use of 3D models facilitated conversation and understanding of cardiac anatomy. Feedback indicated that they found the workshops a positive experience and valued the opportunities to understand their condition and themselves as individuals living with CHD, working with peers and the privilege of reflecting on uniqueness. As one adult participant stated, 'I also truly understood for the first time that this was something that would be with me for the whole of my life…that it is a story which will continue to be written for the rest of our lives, for good or bad it'll never reach its conclusion for as long as we are alive.'